1976
DOI: 10.1071/ph760511
|View full text |Cite
|
Sign up to set email alerts
|

Giant Resonances

Abstract: Aust. J. Phys., 1976, 29, 511-59 A review is given of giant muitipole resonances in nuclei with emphasis on their systematic location, their great strength in terms of an appropriate sum rule and their concentration in a rather narrow region. Capture reactions as a source of information are especially considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…To overcome the repulsive effect of positively charged protons located on the surface of the nucleus, which are weakly bound to the nucleus, the electron density increases, creating a layer of nearly-neutral nucleons, or neutrons, called neutron skin. Experiments have shown that the density of the nucleus is higher than the band forming the surface of the nucleus, which is neutrally charged [30][31][32][33][34][35][36]. Thus, the nucleus is bounded by neutrally charged nucleons, that is, the nucleus is surrounded by so-called neutron skin.…”
Section: Structural Model Of Nucleimentioning
confidence: 99%
“…To overcome the repulsive effect of positively charged protons located on the surface of the nucleus, which are weakly bound to the nucleus, the electron density increases, creating a layer of nearly-neutral nucleons, or neutrons, called neutron skin. Experiments have shown that the density of the nucleus is higher than the band forming the surface of the nucleus, which is neutrally charged [30][31][32][33][34][35][36]. Thus, the nucleus is bounded by neutrally charged nucleons, that is, the nucleus is surrounded by so-called neutron skin.…”
Section: Structural Model Of Nucleimentioning
confidence: 99%